A rare case of visceral leishmaniasis misdiagnosed as systemic lupus erythematosus. Issue 1 (11th October 2021) - Zheng, Mai; Liu, Shuang; Wang, Xiangyu; Li, XingJun; Wang, Nan; Guo, Yulong; Yang, Jingyi; Upreti, Bibhuti; Cui, Ruomei; Xu, Jian
Abstract: Visceral leishmaniasis (VL) is an infectious disease caused by Leishmania donovani and transmitted by sandflies. It can be life‐threatening if not treated. Common clinical features of VL include recurrent fever, pancytopenia, splenomegaly, and a variety of positive autoantibodies, which can lead to a misdiagnosis of systemic lupus erythematosus (SLE). We report the case of a 25‐year‐old woman with VL misdiagnosed as SLE to add to the existing literature on this subject. Highlights: VL patients may present with multiple positive autoantibodies, which could lead to misdiagnosis as autoimmune diseases. When autoimmune diseases such as SLE with atypical clinical manifestations are suspected, some rare infections such as VL are needed to be ruled‐out.